The Electoral Best Practices and Peace Building Strategy Towards Elections In Nigeria - Opeyemi, Iroye Samuel (NIU Journal of Social Sciences, 2020)
The electoral periods in Nigeria has always come down with all forms of activities that can endanger both the electorates and the entire nation most especially as perpetrated by the political urchins either directly or indirectly, thus, creating an atmosphere of threat, intimidation, violence and insecurity. This to certain extent has negatively affected the dispositions of the electorates towards the electoral processes and probably towards the elections results which most often times were adjudged to be not free and fair. The need to therefore proffer viable solutions to this menace motivated the writing of this paper. This paper examines the perceptions and conditions of the electorates during the elections and highlights the mechanism for ensuring the creation of a peaceful and enabling environment during the electoral periods in Nigeria. This research employs analytical research methodology in getting the presented facts in this work. The findings in this research will help to provide proper guidance to the conduct of election and creation of sustainable peaceful and conducive environment during the process of elections in Nigeria. Keywords : Elections, Electorate, Peace-building, Strategy